Experimental analysis of the thermal performance of plastering mortars comprising hybrid phase change materials for increased energy efficiency in buildings - Kheradmand, Mohammad (2013)
Several research studies have forwarded the possibility of incorporating microencapsulated phase change materials (PCM) in plastering mortars for building façades, in pursuit of increased energy efficiency associated to the heat storage capacity of PCM. Nonetheless, most of these studies are centred in the use of a single type of PCM, which is bound to be more adequate for a given season of the year (e.g. winter or summer) than for other seasons, particularly in the case of South-European countries. The study proposed in this work regards the evaluation of the possibility of using more than one kind of PCM (with distinct melting ranges) in plastering mortars, in order to achieve adequately advantageous performance in both heating and cooling seasons. In order to characterize the PCM there are two parameters (enthalpy and phase change temperature) that should be adequately measured. The main purpose of this study was to show feasibility and to evaluate the behaviour of mortars that contain hybrid PCM’s with Differential Scanning Calorimeter testing (DSC). The knowledge obtained from the experimental testing shall establish bases for a framework of numerical simulation of real scale applications, which can be used to ascertain the feasibility of the hybrid PCM concept for increased energy efficiency in buildings.